Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Mengagungkan Allah SWT Dengan Tunduk Pada Perintahnya Kelas VII C di SMPN 4 Jawai Tahun 2025 - Nimas Kumala Sari (PIJAR: Jurnal Pendidikan dan Pengajaran, 2025)
This study aims to improve student learning outcomes by applying a problem-based learning (PBL) learning model on the material of glorifying Allah Swt. by submitting to his commands in class VII C at SMPN 4 Jawai. This type of research is classroom action research (PTK) which consists of II cycles. This research includes four stages, namely planning, implementation, observation and reflection. This research was conducted collaboratively between teachers and observers (researchers). The types of instruments used for data collection are student learning outcomes tests and teacher and student activity observation guideline sheets. The data obtained were analyzed quantitatively to determine individual completeness and classical completeness and qualitative data to determine the activities of students and teachers in the implementation of the problem-based learning model by students and teachers. The results of data analysis showed an increase in student learning outcomes, teacher activities and student activities in each cycle. The increase in learning outcomes is that the classical completeness of students increased from 60.71% (cycle I) to 89.28% (cycle II), or an increase of 28.57%. Meanwhile, the teacher activity value increased from 65.21% (cycle I) to 86.95% (cycle II) with an increase of 21.74%. Likewise, the value of student activity increased from 60.86% (cycle I) to 86.95% (cycle II) with an increase of 26.09%. Based on the results of the data analysis, the research was declared successful because the classical completeness was > 85, the teacher's activity was categorized as very good and the student activity was categorized as very active. Thus it can be concluded that the problem-based learning (PBL) model can improve student learning outcomes on the material of glorifying Allah Swt. by submitting to his commands in class VII C at SMPN 4 Jawai